Ethnoscience of Keris Making: Relevance of Local Knowledge to Scientific Knowledge - Nurul hidayah Nurul; Agil Al Idrus; Agus Abhi Purwoko (Indonesian Journal of STEM Education, 2024)
This study examines the relevance of traditional knowledge and scientific science in the process of making keris in Sakra Village, East Lombok. Keris, as a symbol of Sasak culture, is made using traditional techniques involving scientific concepts such as alloys, thermal expansion, and plastic deformation. This study uses a descriptive qualitative method through observation, interviews, and literature studies. The results show that the traditional technique of making keris can be explained scientifically and is relevant to ethnoscience-based learning. This approach improves science literacy, preserves local wisdom, and develops students' creative thinking skills. The process of making keris can be used as a contextual learning medium to connect science with daily life.